Paschen–Back effect modulation of SO4 2- hydration in magnetized electrolyte toward dendrite-free Zn-ion batteries - Xiayan Yao; Zhi Wang; Jianwei Guo; Guoyu Qian; Hongchen Wang; Xuzhong Gong; Dong Wang (Nature Communications)
Abstract Tuning anionic solvation structures and dynamic processes at solid–liquid interfaces is critical yet challenging for stabilizing Zn metal negative electrodes in Zn-ion batteries, particularly due to the issue of dendrite formation and hydrogen evolution reaction. Here, we show that highly hydrated SO4 2- can be effectively modulated under a strong magnetic field via the Paschen–Back effect on O-H vibrations, which reorients individual water molecules to manipulate Zn2+ solvation and protonated water clusters (H3O+). Molecular dynamics simulations and in situ Raman spectroscopy reveal that the hydrated SO4 2-–H2O complexes promote Zn2+ nucleation and deposition on the (002) plane, with preferential oxygen adsorption inhibiting two-dimensional Zn2+ diffusion. Moreover, magnetizing the electrolyte disrupts the Grotthuss proton-transfer pathway, suppressing H2 evolution and further reducing dendrite formation. By employing inexpensive permanent magnets without external power, this magnetization strategy offers a practical, energy-efficient route to enhance both the stability and performance of zinc-based rechargeable batteries.